2016
DOI: 10.1038/aps.2015.135
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying the cardiac pacemaker: the role of SK4 calcium-activated potassium channels

Abstract: The proper expression and function of the cardiac pacemaker is a critical feature of heart physiology. The sinoatrial node (SAN) in human right atrium generates an electrical stimulation approximately 70 times per minute, which propagates from a conductive network to the myocardium leading to chamber contractions during the systoles. Although the SAN and other nodal conductive structures were identified more than a century ago, the mechanisms involved in the generation of cardiac automaticity remain highly deb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 192 publications
(229 reference statements)
1
31
0
2
Order By: Relevance
“…Pacemaker cells are natural oscillators that cause involuntary muscles and other tissues to contract or dilate. They are spontaneously active neurons with a specialized cell membrane that allows sodium and potassium to cross and generate regular, slow action potentials (around 100 spikes per minute) [17,18]. Modulating input controls the spike frequency.…”
Section: Electroencephalogramsmentioning
confidence: 99%
“…Pacemaker cells are natural oscillators that cause involuntary muscles and other tissues to contract or dilate. They are spontaneously active neurons with a specialized cell membrane that allows sodium and potassium to cross and generate regular, slow action potentials (around 100 spikes per minute) [17,18]. Modulating input controls the spike frequency.…”
Section: Electroencephalogramsmentioning
confidence: 99%
“…K Ca are activated by intracellular Ca 2+ and subsequently generate K + efflux. Recently, studies have indicated that SK4 plays an important role in the automaticity of sinus atrial node and stem cell-derived cardiomyocytes and that SK4 inhibitors significantly reduce automaticity [10,12]. Previous studies have found that SK4 was present in the atrium.…”
Section: The Expression Of P-p38 and C-fosmentioning
confidence: 99%
“…Studies have shown that SK2 and SK4 are expressed in the pulmonary veins (PVs) of dogs and rabbits [9]. A recent study also demonstrated that SK4 is expressed in the human atrium but absent in the ventricle [10].…”
Section: Introductionmentioning
confidence: 99%
“…After years of exploration and practice, there is still room for improvement of symptomatic treatment methods including pharmacotherapy, percutaneous catheter ablation, or pacemaker implantation (Nattel and Carlsson 2006;Carlsson et al 2010;Yamada and Kay 2012;Vernooy et al 2014). Many factors can disrupt cardiac rhythms, including myocardial ischemia, prescription drugs, electrolyte disorders, smoking, alcohol, coffee, physical exercise, mental stimulation, ion channel abnormalities, or genetic defects (Kathiresan and Srivastava 2012;Peyronnet et al 2016;Weisbrod et al 2016;Chrysant 2017;Du et al 2017;Goyal et al 2017). Undoubtedly, defects of cardiac pacemaker cells and the corresponding tissues also disrupt cardiac rhythms (Yazawa et al 2011;Vedantham 2015).…”
Section: Introductionmentioning
confidence: 99%